Design and fabrication of exhaust and fuel systems for a formula student race car / Muhammad Shahrul Aiman Md Shahrir - Md Shahrir, Muhammad Shahrul Aiman (2023)
The Formula Student race car's exhaust system play a crucial role in engine performance and overall speed. For fuel system, it ensure s driver’s safety, comfort, and fuel delivery. The current system is not efficient, leading to high backpressure in the exhaust and danger for driver . To address these issue, the project aims to design and fabricate an optimized exhaust and fuel system s using Computer Aided Design (CAD) software and metal fabrication techniques. The optimized system is expected to reduce backpressure, and improve engine performance, resulting in a faster race car. Also, ensures driver’s safety, efficient fuel delivery and efficient throttle control for the race car. The project involves analyzing the current system, designing the optimized system, and fabricating it to match specifications. The efficient exhaust and fuel system s are essential for the performance of a Formula Student race car and can enhance engine performance and speed.